Sleep and anesthesia Neural correlates in theory and experiment - Hutt, Axel.; SpringerLink (Online service). (New York, NY Springer New York, 2011)
Sleep and anesthesia seem so similar that the task of analyzing the neurological similarities and differences between the two is an obvious research postulate. Both involve the loss of consciousness, or the loss of awareness of external stimuli. Yet when we investigate further, key differences start to manifest themselves?anesthesia is drug-induced while sleep requires no external cause being only the most salient. Other fascinating questions crowd in too: do we dream while under anesthesia, and do we feel pain while sleeping? Examining neural activity associated with sleep and anesthesia can be effected at various levels, from the microscopic, single-neuron level right up to that of whole neural populations. This book aims to reveal the underlying neural mechanisms of sleep and anesthesia by employing a range of experimental techniques and applying theoretical models of neural activity that predict the mechanisms related to both states. Of course, these models offer deeper insights if their assumptions and resulting data can be correlated to experimental findings, and it is these correlations that the book focuses on. As the outcome of workshops on anesthesia and sleep at the 2007 and 2009 Computational Neuroscience Conferences in Toronto and Berlin, the chapters lay out key theoretical issues as well as hot contemporary research topics. It also details experimental techniques on various spatial scales, such as fMRIand EEG-experiments on the macroscopic, and single-neuron and LFP measurements on the microscopic scale.
Foreword: Computing the mind by Anthony Hudetz -- Preface by Axel Hutt -- 1. Sleep and Anesthesia: A Consideration of States, Traits, and Mechanisms by G. Mashour, University of Michigan -- 2. Modelling sleep and general anaesthesia by J. Sleigh, University of Auckland -- Section 1: Sleep -- 3. Quantitative Modeling of Sleep Dynamics by P. Robinson, University of Sydney -- 4. The fine structure of slow-wave sleep oscillations: from single neurons to large networks by A. Destexhe, CNRS Gif-sur-Yvette Paris -- 5. A population network model of neuronal and neurotransmitter interactions regulating sleep-wake behavior in rodent species by V. Booth, University of Michigan -- 6. Neural correlates of human NREM sleep oscillations by P. Maquet, University of Liege -- Section 2: Anesthesia -- 7. A mesoscopic modelling approach to anaesthetic action on brain electrical activity by D. Liley, Swinburne University of Technology -- 8. Progress in modeling EEG effects of general anesthesia: Biphasic response and hysteresis by A. Steyn-Ross, University of Waikato -- 9. EEG modeling in anesthesia: a new insight into mean-field approach for Delta activity generation -- by Behnam Molaee-Ardekani, University of Rennes -- 10. A neural population model of the bi-phasic EEG-power spectrum during general anaesthesia by A. Hutt, INRIA Nancy -- 11. In vivo-electrophysiology of anesthetic action by B. Rehberg-Kluge, Charite Humboldt University Berlin.
Electronic reproduction.
Keywords: Sleep -- Physiological aspects; Anesthesia; Sleep -- physiology; Anesthesia -- methods; Models, Theoretical; Polysomnography -- methods; Electronic books